Abdominal Wall Metastases in Patients With Ovarian Cancer After Laparoscopic Surgery: Incidence, Risk Factors, and Complications. Issue 1 (1st January 2010) - Heitz, Florian; Ognjenovic, Dejan; Harter, Philipp; Kommoss, Steffan; Ewald-Riegler, Nina; Haberstroh, Maren; Gomez, Ruth; Barinoff, Jana; Traut, Alexander; Du Bois, Andreas
Abstract : Objectives: Laparoscopy is the standard procedure to clarify undefined ovarian masses. However, laparoscopy could induce tumor spread in ovarian cancer (OC). The aim of this study was to assess the incidence, the risk factors, and the complications of abdominal wall metastases (AWM) in patients with OC after laparoscopy. Methods: Retrospective study of patients with primary diagnosis of OC who had laparoscopy before cytoreductive surgery and resected port sites in laparotomy between 1999 and 2008 at our institution. Patients with borderline or nonepithelial ovarian tumors were excluded. Results: Of 537 patients with a first diagnosis of OC, 101 had laparoscopy before definitive operation after a median of 31 days. Histological examination at final cytoreductive surgery of the port sites was conducted in 66 patients, whereas 31 patients (47%) showed AWM. Patients experiencing AWM had higher tumor stages and peritoneal carcinomatosis. Ascites with more than 500 mL was a further independent risk factor for AWM (odds ratio: 7.2; 95% confidence interval, 1.5-35.8; P = 0.016). Abdominal wall metastasis did not impact on survival in our cohort; however, affected patients showed significant larger abdominal wall resections (mean [SD]): 41.0 (angled brace 13.1) cm 2 versus 9.1 (angled brace 1.4) cm 2 in comparison with patients without AWM ( P = 0.013), and 2 patients developed abdominal wall recurrences. Conclusions: The incidence of AWM in patients experiencing OC was considerably high when laparoscopic surgery was conducted before cytoreductive surgery. Patients experiencing AWM seem to have more surgical burden. However, our series did not show a dramatic impact of AWM on long-term outcome. Patients with highly suspected advanced OC and ascites with more than 500 mL should be referred directly to a gynecologic oncologist who is able to balance risks of laparoscopic staging and direct cytoreductive surgery.